Direct conversion of raw wood to TEMPO-oxidized cellulose nanofibers. (15th June 2021) - Kaffashsaie, Elmira; Yousefi, Hossein; Nishino, Takashi; Matsumoto, Takuya; Mashkour, Mahdi; Madhoushi, Mehrab; Kawaguchi, Hideo
Graphical abstract: Highlights: TEMPO-oxidized cellulose nanofibers (TOCN-D) were directly produced from raw wood. Purification and oxidation of cellulose were done simultaneously. TOCN-D and TOCN-C (produced from cellulose fibers) had the same properties. Nanopapers produced from TOCN-D and TOCN-C had the same properties. TOCN-D production method is cheaper, faster and simpler compared to that of TOCN-C. Abstract: A direct production route of cellulose nanofibers (TOCN-D) from raw wood particles of paulownia using simultaneous bleaching and TEMPO oxidation process was specifically investigated and introduced. For comparison, we prepared cellulose nanofibers (TOCN-C) through a common route of TEMPO oxidation of cellulose fibers, and cellulose nanofibers with disk grinding (GCNF). FE-SEM analysis showed that the average diameter of TOCN-D (5 ± 3 nm) was similar to that of TOCN-C (6 ± 3 nm). XRD results confirmed that the crystal properties of TOCN-D and that of TOCN-C were almost the same. TOCN-D and TOCN-C showed similar chemical, thermal and optical properties in FTIR, TGA and transparency tests, respectively. The nanopaper made from TOCN-D showed high Young's modulus (13.8 GPa) and tensile strength (233 MPa), which were similar to those of TOCN-C nanopaper. Owing the aforementioned similarities, it is concluded that the TOCN-D produced through direct route is a technically, environmental-friendly and economically valuable product.